Penerapan Metode VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) dalam Pemilihan Air Conditioner Terbaik - Mesran Mesran; Kurnia Ulfa; Dito Putro Utomo; Ida Rizky Nasution (UIN Sumatera Utara, 2020)
Indonesia is a tropical country which consists of summer and rainy season. During the summer the room temperature will be high, so that will cause people who are in the room will feel uncomfortable or hot. To create comfortable conditions, air conditioning is needed. SPK is part of a computer-based information system. There are several stages in the decision support system, namely defining the problem, collecting relevant and appropriate data, processing data into information, and determining alternative solutions. The number of AC products on the market makes people feel difficult in choosing the right AC so that a decision support system is made. The VIKOR method focuses on ranking and choosing from a set of samples with conflicting criteria, which can help decision-makers to get a decision.